A Kantian Reconciliation of Moral Realism and Moral Supervenience - LYONS, MICHAEL (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Philosophy, 2018)
The 'Moral Supervenience' thesis is a deeply intuitive and popular one within philosophy, and can be defined as follows: "There can be no changes in any moral properties without at least some kind of change in non-moral properties." What this thesis basically states is that there is a necessary connection (knowable on an a priori basis) between the moral and non-moral properties of any given situation. In other words, when you have two actions that at least appear identical, they can only have different moral properties if the non-moral properties are different in a morally relevant way (for instance, cutting someone may, on the face of it, be wrong, unless a surgeon is doing the cutting with informed consent, for example). When this thesis is combined with moral realism (i.e., the view that there are moral facts that are objectively true or false on an attitude-independent basis), Simon Blackburn claims that a mystery is created: how is it that there can be this necessary connection between moral and non-moral properties, when there is no logical entailment from one to the other? Blackburn advocates an alternative account of morality: rather than there being objective attitude-independent moral facts, he claims that moral judgements necessarily have attitudinal content. He also thinks that his account better explains supervenience than moral realism, and thus claims that we ought to accept his account. In this dissertation, my aim is to identify how a moral realist could respond to Blackburn's argument. After setting out the view of moral realism, the notion of moral supervenience, and Blackburn's argument in greater detail in the first chapter, as well as its historical inspiration dating back to J. L. Mackie, I aim to categorise the responses that have been, or otherwise could be, made into at least four different strategies. I will then identify which of the viable strategies is the most plausible, devoting a chapter to each. I will then argue that Kant would have been able to defend Moral Supervenience as a conceptual thesis, by justifying the thesis analytically as a conceptual requirement of the systematic behaviour of moral facts, but equally claim that the proposition that moral facts do supervene can only be justified synthetically, and therefore could have responded to the challenge on a realist basis. However, even if a realist interpretation of Kantian Ethics could provide a viable answer to the challenge, Blackburn's argument might still be taken to be sound if his expressivism is taken to be preferable to the Kantian synthetic practical justification of moral facts. Yet Blackburn's very own Quasi-Realist project depends upon a kind of synthetic practical justification of its own, which seems fundamentally akin to that of Kant – that is, the practical legitimacy of our moral discourse with its "realistic seeming nature". Unlike Kant though, Blackburn is committed to the claim that all moral discourse must have some attitudinal content behind it, and it is not clear how this can be explained. A realist interpretation of Kant can be preferable to Blackburn's after all, on the basis that it gets right to the heart of the mystery behind his modal challenge, but does not have to explain how all moral discourse necessarily has attitudinal content behind it.
APPROVED